The Effects of Multitasking on Auditors’ Judgment Quality - Mullis, Curtis E.; Hatfield, Richard C. (Contemporary Accounting Research, 2018)
Abstract Auditors must frequently multitask in order to complete their work efficiently. However, the potential impact of multitasking on auditors’ judgment quality is poorly understood. Using Ego Depletion Theory and a laboratory experiment, we predict and find that auditors become less able to identify seeded errors after multitasking, and that this effect is most prominent in the identification of conceptual, rather than mechanical, errors. These negative consequences of multitasking are mitigated when auditors are exposed to an intervention based on a theoretical countermeasure of replenishing depleted self‐control resources, in that multitasking auditors identify more seeded errors with the intervention than without. Given that multitasking is a pervasive feature of the current audit environment, these findings have direct implications for audit practice. Beyond identifying multitasking as a cause of impaired performance in auditing, this study's results provide initial evidence that such negative effects can be mitigated, resulting in improved audit quality and, by extension, improved financial statement quality.